PENERAPAN PENDEKATAN MATEMATIKA REALISTIK (RME) UNTUK MENINGKATKAN PEMAHAMAN MATEMATIS PADA MATERI POKOK PERBANDINGAN DAN SKALA - Widyawati, Wiwid (2014)
The background of this research was the low students' comprehension mathematics as revealed by their average scores which were under KKM. This was caused by the used of conventional methods, teachers organized the learning process monotonously, which were uninteresting and boring. Based on those problems, the researcher made an attempt to implement the realistic mathematics approach as an approach which could improve learning process in mathematics class. The objectives of this research were (1) to obtain the depiction of the implementation process of learning which applied the realistic mathematics approach (2) to gain the depiction of the students' mathematics comprehension improvement after the implementation of the realistic mathematics approach. The method used in this research was class action research by adopting Kemmis and Mc. Taggart model which was done in two cycles. The findings showed that students' comprehension from cycle I to cycle II increased. In addition, students' evaluation scores improved in each scores. In cycle I, students' average scores were only 66, 57 within completeness percentage 69,7%, meanwhile in cycle II the students' average scores were 85,75 within completeness percentage 90,9%. Based on those findings, there were suggestion offered by the researcher, those are: (1) the learning which implemented the realistic mathematics approach could be an alternative for the teachers in teaching mathematics in school (2) the school had better provide facilitate both media and infrastructure (3) ask the teachers to be more creative in displaying context (4) give positive input to the researcher as provisions to develop and improve the mathematics learning in the future.